Coco-products Philippines - Bangayan, Anselma L. (College of Engineering, 1973)
Plant location: Sta. Cruz, Davao -- Plant size: 2,175 sq.m. -- Plant capacity: 20,000 nuts/day, 300 days/year -- Capital investment: 6,951,000 -- Total product cost: 4,680,000 -- Annual sales: 9,513,663 -- Break-even point: 24% of max. capacity -- Shut-down point: 10% of max capacity -- Annual rate of return on investment before tax: 69.5% -- Annual rate of return on investment after tax: 40% -- Pay-out time: 2 years and 11 months